VALIDITAS PREDIKTIF TES MASUK PADA STKIP MUHAMMADIYAH PRINGSEWU LAMPUNG - Saikhoni, author (JURNAL FOKUS KONSELING, 2015)
The Quality of higher education is determined by the quality of student input. The student of higher education as a raw input has a strategic value because of its position as the subject that developed in the educational process. To get the qualified student, it is needed a valid test instrument for the student and able to measure something that should be measured. College admission test, especially in STKIP Muhammadiyah of Pringsewu Lampung is a test that is expected able to estimate or predict the success of student in university classes in the future.Keywords: Validity, Test Score, Learning Achievement